Aerodynamics of marine vessels - Muhammad Al-Muzakkir Kamsani. (2012)
This report presents observations and analysis of the detailed turbulent flow over a Marine Vessel specifically a Cargo Vessel. It can also be taken as an aerodynamic study over a forward-facing step. Computational Fluid Dynamic analysis on ANSYS FLUENT software was used to predict and obtain an approximation of the flow outcome based on a scale model of the specific vessel. The model was also used in a water and wind tunnel test for comparison with the computational results. More precise flow visualization was obtained in the water tunnel test which had also provided a rough estimation of the critical point of interest. The wind tunnel test was performed to obtain the numerical data which were then used to locate the maximum flow velocity or the wind power over the superstructure of the vessel model by Excel Computation Method (The concept of integrating the Velocity Profile from the Wind Power Equation). The existence and location of a circulation phenomenon was observed both in ANSYS FLUENT analysis and water tunnel test. It was found that the maximum wind power depends on the height of the step and the flow velocity of the free stream. The maximum wind power was located to be at 15mm (horizontally) from the tip of the step and 30mm (vertically) above the surface of the step for the specific scaled model used.